ECED 2022
DOI: 10.55439/eced/vol23_iss1/a53
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Assessment of Resources and Services Affecting Tomorka (Small Households) Farm in Rural Areas and Their Income

Abstract: The research examines the role and importance of income from tomorka (small household) farm activities in rural areas. The factors influencing the formation of income from tomorka farm activities were also assessed economically through tobit regression model, and a VIF (Variance inflation factor) test was performed to determine their multicollinearity. Anonymous surveys of 170 landowners in 4 districts of Samarkand region have been used in the analysis. The increase in income from tomorka farm is due to the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The average arable land in homesteads is 7,323 hectares, which can limit the possibility of raising productive livestock breeds. The age, gender, education and number of family members (Pardaev, 2021) of the owners of the estate are important for the change of the income from the tomorka farm activities (Muratov, 2021). However, the average age of the respondents is 48.1 years, and they are at working age.…”
Section: Methodsmentioning
confidence: 99%
“…The average arable land in homesteads is 7,323 hectares, which can limit the possibility of raising productive livestock breeds. The age, gender, education and number of family members (Pardaev, 2021) of the owners of the estate are important for the change of the income from the tomorka farm activities (Muratov, 2021). However, the average age of the respondents is 48.1 years, and they are at working age.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the infrastructure facilities are not fully formed at the stages of delivering the product to consumers [9] [10]. In most cases, processing companies use their monopoly power to force smallholders to sell their products at low prices [11]. In addition, processing enterprises do not have the opportunity to quickly accept the product during the peak season, and they deliberately do not fulfill the terms of the contractual agreements between the entities to reduce prices.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical observations show the highest rate among the production of vegetables and grapes, the amount of which was three times higher than in previous periods . Several studies found that sociodemographic factors of agricultural producers' statistically significant impact the household income changes (Muratov, 2021). Smallholders would prefer mixed crop production and consumption, and sell the rest of production by contract through the agri-food supply chain.…”
mentioning
confidence: 99%